Ion exchange equilibria involving aluminum in a kaolinitic Ultisol - Pleysier, J.L.; Juo, A.S.R.; Herbillon, A.J. (Wiley, 1979)
Cation exchange equilibria in an acid Ultisol profile involving K-Al, Ca-Al, K-Ca, Na-K, and Na-Ca exchanges were studied. Selectivity coefficients, surface activity coefficients and free energy changes were computed using the thermodynamic formulations. In exchange equilibria involving Al, the magnitude of selectivity coefficients Kc, was affected by pH, surface composition, and hydrolysis of Al. In equilibria not involving Al, good reversibility for K-Ca, Na-K and Na-Ca exchanges was obtained. Potassium was selectively adsorbed in all horizons of the profile. The over-all selectively sequence follows the order of K>Al>Ca≈Na.